Tolerance Analysis and Optimization of Static Assembly of RV Reducer based on 3DCS - Xiongwei Xie; Honghai Xu; Tong Guan (Jixie chuandong)
In order to improve the assembly yield of RV reducer， combined with its assembly dimension chain design parts tolerance，the use of CATIA is for three-dimensional modeling of RV reducer. Combined with 3D tolerance analysis software 3DCS， the relative dimension tolerance and geometric tolerance are added to the parts，eccentricity and clearance of measurement parameters are set，and 3DCS tolerance simulation model is established to simulate the actual static assembly process, tolerance optimization and sensitivity analysis of parts are carried out. After optimization， the backlash is 0.25'~1'， which meets the requirement of backlash. The clearance between the cycloidal wheel and the pin gear is greater than or equal to 0.001 mm，and the sensitivity analysis result has certain reference value for the tolerance design of the RV reducer.